Effect of Emotional State on Nutrition Behavior in Working And Non-Working Women Living in Manavgat District. - Tayfur, Muhittin; Ulucay , Vahibe; Koseoglu, Sabiha Zeynep Aydenk (Progress in Nutrition, 2020)
BACKGROUND/OBJECTIVES: The aim of this study is to evaluate whether there is the relationship between these cases by comparing moods like depression, stress, anxiety, nutrition behaviors, food preferences and anthropometric measurements of working and non-working women living in Manavgat district. MATERIALS/METHODS: This study was conducted with total of 210 women, of whom 105 were working and 105 were not nonworking, between the ages of 25-45. Participant’s demoggraphic characteristics, antropometric measurements, food consumption over the last 24 hours, depression, anxiety and stress level, and nutritional behavior. RESULTS: The difference between stress, anxiety and cognitive restriction scores of working and non-working women was statistically significant (p